Penyuluhan Alat Kontrasepsi Pada Pasangan Usia Subur Di Dusun 2 Desa Pukdale Kecamatan Kupang Timur Kabupaten Kupang - Maria Vilastry Nuhan; Matilda Bupu Ria; Roslin E. M. Sormin (Jurnal Nusantara Berbakti, 2023)
A quality family is a family that is formed based on a valid marriage and is characterized by being prosperous, healthy, advanced, independent, having an ideal number of children, forward-looking, responsible, harmonious and devoted to God Almighty. To be able to create a quality family, they will feel the need to use family planning tools. To help them choose a suitable family planning tool, they need to be given family planning counseling. The purpose of contraception is to avoid/prevent pregnancy as a result of a meeting between a mature egg cell and a sperm cell. The aim of family planning is to form a happy and prosperous family in accordance with the socio-economic conditions of a family by regulating the birth of children, increasing the age of marriage, increasing the resilience and welfare of the family so that it can meet its living needs. The purpose of marriage is to form a happy and eternal family. For this reason, husband and wife need to help and complement each other, so that each can develop their personality, help and achieve spiritual and material prosperity.